PENGARUH KUALITAS SUMBER DAYA MANUSIA, PARTISIPASI MASYARAKAT DAN PERILAKU KEPEMIMPINAN TERHADAP PENGELOLAAN DANA DESA DENGAN KOMITMEN PADA TUJUAN SEBAGAI VARIABEL MODERASI - Firhan Baihaqi Harahap; Afrah Junita; Tuti Meutia (Fakultas Ekonomi Universitas Samudra, 2020)
This study was conducted to determine the effect of human resources, community participation, and leader behavior on village fund management with a commitment to objectives as moderation variables. The sample selection in this study used the purposive sampling method. The number of samples used was 54 respondents. The data obtained were analyzed using the Partial Least Square (PLS) analysis technique. The equation models analyzed are the outer model, inner model, and hypothesis testing. The results of this study show that: (1) Human Resources Quality (KSDM) has no significant effect on Village Fund Management (2) Community Participation (PM) has a significant effect on Management Village Funds (3) Leadership Behavior (PM) has a significant effect on Village Fund management (4) Commitment to goals (KPT) has a significant effect on Village Fund Management (5) Quality of Human Resources (KSDM) in Moderation with Commitment to goals has no significant effect Village Fund Management (6) Community Participation (PM) in Moderation with Commitment to goals does not have a significant effect on Village Fund Management (7) Leader Behavior in Moderation with Commitment to goals has no significant effect on Village Fund Management.